Financial decision‐making and self‐awareness for financial decision‐making is associated with white matter integrity in older adults. Issue 5 (4th January 2022) - Sunderaraman, Preeti; Gazes, Yunglin; Ortiz, Gema; Langfield, Christopher; Mensing, Ashley; Chapman, Silvia; Joyce, Jillian L.; Brickman, Adam M.; Stern, Yaakov; Cosentino, Stephanie
Abstract: Financial decision‐making (FDM) and awareness of the integrity of one's FDM abilities (or financial awareness) are both critical for preventing financial mistakes. We examined the white matter correlates of these constructs and hypothesized that the tracts connecting the temporal–frontal regions would be most strongly correlated with both FDM and financial awareness. Overall, 49 healthy older adults were included in the FDM analysis and 44 in the financial awareness analyses. The Objective Financial Competency Assessment Inventory was used to measure FDM. Financial awareness was measured by integrating metacognitive ratings into this inventory and was calculated as the degree of overconfidence or underconfidence. Diffusion tensor imaging data were processed with Tracts Constrained by Underlying Anatomy distributed as part of the FreeSurfer analytic suite, which produced average measures of fractional anisotropy and mean diffusivity in 18 white matter tracts along with the overall tract average. As expected, FDM showed the strongest negative associations with average mean diffusivity measure of the superior longitudinal fasciculus ‐temporal (SLFT; r  = −.360, p  = .011) and ‐parietal ( r  = −.351, p  = .014) tracts. After adjusting for FDM, only the association between financial awareness and average mean diffusivity measure of the right SLFT ( r  = .310, p  = .046) was significant. Overlapping white matter tracts were involved in both FDM and financial awareness. More importantly, these preliminary findings reinforce emerging literature on a unique role of right hemisphere temporal connections in supporting financial awareness. Abstract : Financial decision‐making and awareness of the integrity of one's financial decision‐making abilities (or financial awareness) are both critical for preventing financial mistakes. Overlapping white matter tracts were involved in both financial decision‐making and financial awareness. More importantly, our findings reinforce emerging literature on a unique role of right hemisphere temporal connections in supporting financial awareness.